A genome-wide association study identified SNP markers and candidate genes associated with morphometric fruit quality traits in mangoes - Shamseldeen Eltaher; Jin Li; Barbie Freeman; Sukhwinder Singh; Gul Shad Ali (BMC Genomics)
Abstract Background Mangoes (Mangifera indica L.) are a widely grown fruit tree crop across the world, but breeding new varieties can take 15-20 years due to its long juvenile period and high heterozygosity. Marker-assisted selection can accelerate breeding new mango cultivars with desirable traits for fruit quality, storage, horticulture, pest and disease resistance, and nutrition. Results To achieve this, a genome-wide association study (GWAS) was conducted to discover molecular markers for 14 morphometric and economically important fruit traits of 161 mango accessions with diverse genetic backgrounds. These traits included pulp and brix; fruit weight, length, thickness, and width; stone weight, length, thickness, and width; and seed weight, length, thickness, and width. In this report, we employed the fixed and random model circulating probability unification (FarmCPU) model for conducting GWAS using 135,079 high-quality SNP markers. These analyses revealed 103 SNPs that were significantly associated with these traits. Of these markers, 7 were commonly associated with different traits, while 96 markers were uniquely associated with specific traits. Conclusions To choose the most promising mango accessions for future breeding and for closing genetic gaps among the accessions and increasing genetic diversity, a new selection method is suggested based on phenotypic traits such as high-yielding mango fruit cultivars, number of reference alleles, and genetic distance among the selected genotypes. Based on these criteria, 20 accessions were identified as the most promising parents for crossing to produce high mango yield. Gene annotation of the significant markers revealed candidate genes coding for important proteins, enzymes, and transcription factors associated with fruit development traits.